Bioavailability Comparison of Two Zopiclone Formulations in Healthy Colombian Volunteers (2015)
ABSTRACT: Zopiclone is a hypnotic short-acting agent used in the treatment of primary insomnia. The aim of this study was to compare the Bioequivalence of two formulations of Zopiclone available in the Colombian market: Zopiclone 7.5 mg commercialized as Zopiclone MK® and Zopicloteg TG® (Test product) manufactured by Tecnoquímicas S.A (Cali, Col.) and Imovane® (Reference product) from Sanofi-Aventis Farmacéutica Ltda (Brasil). With this purpose, a single dose, randomized, crossover, with two periods, two sequences and a washout period of one week study was developed. Blood samples were drawn from 0 to 24 hours following the drug administration. Zopiclone plasma levels were determined by HPLC method, validated under the FDA parameters. The 90% confidence intervals for the ratios of the ln AUC0-∞ and ln Cmax means between the Test and Reference product were constructed. The 80/125 rule was used as bioequivalence criterion. The study was conducted in 26 healthy volunteers. The estimated pharmacokinetic parameters for Zopiclone, either for the Test product or Reference product were Cmax 72.815 ± 20.54 ng/mL, 74.315 ± 18.04 ng/mL; AUC0-t 467.297 ± 92.21 ng.h/mL, 460.996 ± 115.81 ng.h/mL, and AUC0-∞ 560.298 ± 118.58 ng.h/ mL, 543.549 ± 136.97 ng.h/mL, respectively. The 90% confidence intervals for the ratio between the averages of ln-transformed data of AUC0-∞ and Cmax were 97.38% - 110.59% and 89.97% - 104.84%, respectively. Conclusion: In the present study of single dose, the Test product, Zopiclone 7.5 mg, meets the Bioequivalence criterion regarding the rate and extent of absorption.